Kajian Ekranisasi Novel After Met You Karya Ari Irham Dan Dwitasari Dalam Bentuk Film After Met You Sutradara Patrick Effendy - Namis Namis; Dian Hartati (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
The background of this research is that there are differences in the story in the After Met You film which was adapted from a novel with the same title. The purpose of this study is to describe the forms of shrinkage, addition, and variation changes that appear in the process of transforming a novel into a film based on ecranization studies using descriptive qualitative methods. The data sources for this research were the novel After Met You by Ari Irham and Dwitasari and the film After Met You directed by Patrick Effendy. Data collection was carried out by reading, observing, and noting techniques. Data processing is done by reading novels and watching films, noting changes, analyzing the forms of change, and describing aspects of these changes. The results of the research show that shrinking, adding, and changing variations that appear from novel to film are found in the characters, plot, and setting. The novel and film After Met You are different, but the theme, point of view, style of language, and message in the novel are still the same when they are filmed.